2021
DOI: 10.1371/journal.pone.0245439
|View full text |Cite
|
Sign up to set email alerts
|

Impact of integrating objective structured clinical examination into academic student assessment: Large-scale experience in a French medical school

Abstract: Purpose Objective structured clinical examinations (OSCE) evaluate clinical reasoning, communication skills, and interpersonal behavior during medical education. In France, clinical training has long relied on bedside clinical practice in academic hospitals. The need for a simulated teaching environment has recently emerged, due to the increasing number of students admitted to medical schools, and the necessity of objectively evaluating practical skills. This study aimed at investigating the relationships betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In our opinion, these results suggest that OSCE brings and added value to MCQs and other traditional examination modalities by evaluating a large variety of skills and in a different way: for instance, MCQs assess mainly medical knowledge and have little ability to assess clinical skills [ 23 ]. Consistently with other studies we observed a significantly larger distribution of grades obtained at OSCE compared to grades from other academic evaluation modalities [ 11 ]. This underlies the potential discriminating power of OSCE for student ranking.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In our opinion, these results suggest that OSCE brings and added value to MCQs and other traditional examination modalities by evaluating a large variety of skills and in a different way: for instance, MCQs assess mainly medical knowledge and have little ability to assess clinical skills [ 23 ]. Consistently with other studies we observed a significantly larger distribution of grades obtained at OSCE compared to grades from other academic evaluation modalities [ 11 ]. This underlies the potential discriminating power of OSCE for student ranking.…”
Section: Discussionsupporting
confidence: 93%
“…This raises the question of the real added value of these evaluations. Matet et al showed that OSCE increased the discriminatory capacity of current evaluations modalities in French medical schools [ 11 ]. Furthermore, Pugh et al showed a correlation ranging from 0.305 ( p = 0.002) to 0.516 ( p < 0.001) between scores from an OSCE progress test and the written component of the national high-stakes examination [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chan et al [12] tested if experiences in public speaking or performances (music, arts, drama) affected the results of an OSCE examination and found modest positive effects. Matet et al [13] showed for a French medical school that OSCE results in behaviouroriented stations (weakly) correlate with higher traineeship skills, while competence-oriented stations had only ties with performances in MC-exams. Kirton and Kravitz [14] concluded that OSCEs and MC-exams measure different competencies by explicitly targeting clinical skills.…”
Section: Related Literaturementioning
confidence: 99%